The Constitution of Boundaries: How the Embeddedness of Organizational Users Structures the Transfer of their Knowledge - Roth, Philip; Diefenbach, Nadine (NOvation — Critical Studies of Innovation, 2022)
Private and organizational users are widely treated as equal in the literature on the integration of users in innovation projects. Based on a practice-theoretical perspective, we argue in this paper that this equation is inconsistent and inadequate. While users are conceptualized as competent and embedded when it comes to the genesis of their user knowledge, both factors are ignored when their involvement in the innovation process is considered. Drawing on empirical findings on interorganizational knowledge transfer, we show that the social, formal, and material embeddedness of organizational users crucially structures their integration. By elaborating the role of different structural dimensions in detail, we highlight the distinctive features of organizational users. In doing so, we further develop a heuristic that enables a detailed and adequate analysis of their integration.